Conventional shoulder arthroplasty in the athlete - Watson, J. D.; Murthi, A. M. (Operative techniques in Sports Medicine, 2008)
Humeral head replacement and total shoulder arthroplasty are successful procedures for improving pain and function for patients with glenohumeral arthritis and intact rotator cuff. Shoulder replacement is becoming more commonplace in younger patients and in an elderly population, with increasing numbers participating in sports. Therefore, many patients have greater expectations of postoperative function, including return to athletics. Before surgery, it is important to counsel the patient regarding the types of activities that are safe and those that are not recommended. Patient expectations can also be managed by evaluating the preoperative level of function and the cause of the glenohumeral arthritis. In general, patients with greater athletic aptitude before surgery will have an easier time returning to sports. Postoperatively, the rehabilitation program is designed to first restore range of motion and improve function in activities of daily living. At 3 months postoperatively, the rehabilitation program becomes more individualized for each patient and sports-specific training is allowed. Performing lesser tuberosity osteotomy when repairing the subscapularis might allow for more reliable healing and greater function after surgery. Ultimately, patient satisfaction with the outcome of shoulder replacement is dependent on a combination of preoperative expectations for athletic participation after surgery and postoperative subjective assessment of symptoms and function.